Validity of an established metabolic disorder index as a predictor for metabolic eliminations in endurance horses - Mohd Rajdi, Nur Zul Izzati; Mohd Adzahan, Noranizan; Adamu, Lawan; Abdullah, Rasedee (Taylor and Francis Group, 2018)
Endurance horses are usually eliminated from the race due to lameness, metabolic ailments or technical reasons. The purpose of the study was to determine the validity and reliability of the metabolic disorder index (MDI) in predicting metabolic eliminations in endurance horses during an endurance race. Fifty-four endurance horses competing on two local endurance tracks were involved in the study. Blood samples were collected a day prior to the event to determine packed cell volume (PCV), chloride (Cl−), interleukin-6 (IL-6), creatine kinase (CK) and glutathione reductase (GR) concentrations from all participating horses. These parameters were used for the determination of metabolic disorder index in endurance horses at rest (one day before the competition). All data were statistically analysed. In 40, 80 and 120 km race distances, the successfully completed horses had a significant lower serum concentration of CK and a significant higher serum concentration of Cl− than the eliminated horses (P < .05). There were no significant differences in PCV, serum concentrations of IL-6 and GR between the successfully completed and eliminated horses in the 40, 80 and 120 km race distances. The MDI at the rest one day before the race could predict potential of metabolic eliminations in endurance horses with at least 78.26%, 80% and 83.33% accuracies in 40, 80 and 120 km race distances. The sensitivity of the MDI was 81.82%, 80% and 100% in the 40, 80 and 100 km race distances. The specificity of the MDI was 80% for the 80 km race distance and 75% for the 40 and 120 km race distances. In conclusion, the metabolic disorder index is a reliable method for the prediction of metabolic eliminations in endurance horses participating in endurance races.